Impact of Spiritual Intelligence on Organizational Performance - Malik, Muhammad Shaukat; Tariq, Sana (International Review of Management and Marketing, 2016)
This study reveals that spiritual intelligence plays a positive and significant role on the quality of work. In this study the work was done in finding that variables such as organizational culture and demographic facts (gender, age & education) act as moderators between the relationship of spiritual intelligence and organizational performance. Population of this study was employees of banks. Sample size was 300. Primary and secondary data were used in this research. Data was analyzed by using statistical software SPSS (16) versions. The study evaluated that there is significant positive relationship between spiritual intelligence and organizational financial performance in terms of ROA and Tobin’s Q value. From the results of this study one can interpret that the spiritual intelligence increases the organizational performance while age, gender, education and organizational culture act as a moderator on their relationship. This research will motivate the managers to enhance spiritual intelligence of employees to increase efficiency and effectiveness. Keywords: Spiritual intelligence, Organizational culture, Demographic variable JEL Classifications: J11, M12, M14